2011
DOI: 10.1097/iae.0b013e318207d1b9
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Daptomycin

Abstract: Purpose To determine the ocular toxicity of intravitreally injected daptomycin, a novel antibiotic for treatment of vancomycin-resistant organisms, and its efficacy in treating intraocular infection with coagulase-negative Staphylococcus epidermidis. Methods Toxicity study: Four doses of intravitreal daptomycin were injected (75, 188, 375 and 750 micrograms) into one eye of Dutch belted rabbits (n=3 per dose). Clinical examination, electroretinography (ERG) and histologic analysis was performed pre-injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 49 publications
0
15
0
1
Order By: Relevance
“…It demonstrates good in vitro bactericidal activity for vancomycin-resistant strains of bacteria accounting for endophthalmitis, including S. epidermidis , S. aureus , S. pneumoniae , E. faecalis , and E. faecium [12]. Comer and colleagues demonstrated that administration of 200 μg of intravitreal daptomycin was safe and efficacious in a rabbit model of bacterial endophthalmitis [13]. Tigecycline is a glycylcycline antibiotic that binds to the 30S ribosomal subunit to inhibit protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrates good in vitro bactericidal activity for vancomycin-resistant strains of bacteria accounting for endophthalmitis, including S. epidermidis , S. aureus , S. pneumoniae , E. faecalis , and E. faecium [12]. Comer and colleagues demonstrated that administration of 200 μg of intravitreal daptomycin was safe and efficacious in a rabbit model of bacterial endophthalmitis [13]. Tigecycline is a glycylcycline antibiotic that binds to the 30S ribosomal subunit to inhibit protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…47-52 Hernandez-Da Mota et al (2011) and Stroh et al (2012) reported cases of endophthalmitis caused by vancomycin-resistant Staphylococcus aureus which were successfully treated with intravitreal quinupristin/dalfopristin. 47, 48 A literature review showed two case reports (Buzzaco et al, 2012 and Sim et al, 2016) of endophthalmitis caused by vancomycin-resistant gram-positive cocci which resolved completely with the use of intravitreal daptomycin.…”
Section: Alternative Intravitreal Antimicrobialsmentioning
confidence: 99%
“…В настоящее время предложены для лечения ванкомицин-резистентных интраокулярных инфекций новые антибиотики, кото-рые обладают высоким профилем безопасности. Однако связанные с этим исследования пока ограничены докли-ническими испытаниями, в которых уже продемонстри-рована их перспективность [32].…”
Section: Introductionunclassified